A pre-therapeutic coating for medical devices that prevents the attachment of Candida albicans - Diego Vargas-Blanco; Aung Lynn; Jonah Rosch; Rony Noreldin; Anthony Salerni; Christopher Lambert; Reeta P. Rao (BMC, 2017)
Abstract Background Hospital acquired fungal infections are defined as "never events"-medical errors that should never have happened. Systemic Candida albicans infections results in 30-50% mortality rates. Typically, adhesion to abiotic medical devices and implants initiates such infections. Efficient adhesion initiates formation of aggressive biofilms that are difficult to treat. Therefore, inhibitors of adhesion are important for drug development and likely to have a broad spectrum efficacy against many fungal pathogens. In this study we further the development of a small molecule, Filastatin, capable of preventing C. albicans adhesion. We explored the potential of Filastatin as a pre-therapeutic coating of a diverse range of biomaterials. Methods Filastatin was applied on various biomaterials, specifically bioactive glass (cochlear implants, subcutaneous drug delivery devices and prosthetics); silicone (catheters and other implanted devices) and dental resin (dentures and dental implants). Adhesion to biomaterials was evaluated by direct visualization of wild type C. albicans or a non-adherent mutant edt1 −/− that were stained or fluorescently tagged. Strains grown overnight at 30 °C were harvested, allowed to attach to surfaces for 4 h and washed prior to visualization. The adhesion force of C. albicans cells attached to surfaces treated with Filastatin was measured using Atomic Force Microscopy. Effectiveness of Filastatin was also demonstrated under dynamic conditions using a flow cell bioreactor. The effect of Filastatin under microfluidic flow conditions was quantified using electrochemical impedance spectroscopy. Experiments were typically performed in triplicate. Results Treatment with Filastatin significantly inhibited the ability of C. albicans to adhere to bioactive glass (by 99.06%), silicone (by 77.27%), and dental resin (by 60.43%). Atomic force microcopy indicated that treatment with Filastatin decreased the adhesion force of C. albicans from 0.23 to 0.017 nN. Electrochemical Impedance Spectroscopy in a microfluidic device that mimic physiological flow conditions in vivo showed lower impedance for C. albicans when treated with Filastatin as compared to untreated control cells, suggesting decreased attachment. The anti-adhesive properties were maintained when Filastatin was included in the preparation of silicone materials. Conclusion We demonstrate that Filastatin treated medical devices prevented adhesion of Candida, thereby reducing nosocomial infections.